Regime legitimacy in contemporary China [ institutional change and stability - Heberer, Thomas; Schubert, Gunter , 1963- (Routledge contemporary China series, 2009)
"Using in-depth case studies of a wide-range of political, social and economic reforms in contemporary China this volume sheds light on the significance and consequences of institutional change for stability of the political system in China. The contributors examine how reforms shape and change Communist rule and Chinese society, and to what extent they may engender new legitimacy for the CCP regime and argue that authoritarian regimes like the PRC can successfully generate stability in the same way as democracies."--Publisher's description